ANALISIS KOMUNIKASI PERSUASIF PEONY ECOHOUSE DALAM MENINGKATKAN KESADARAN LINGKUNGAN MELALUI PENDEKATAN TEORI GOALS-PLANS-ACTION - Galih Andriansyah Putra; Mufid Salim (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2022)
Environmental awareness has become a hot topic in recent years around the world. One of them is Indonesia. This awareness is present due to the many disasters that come from human error response to the environment and its changes. Today's environmental problems are widely discussed, because it has been seen that there is environmental pollution caused by human actions. Peony Ecohouse as one of the first eco-friendly grocery stores in the Special Region of Yogyakarta has contributed to increasing environmental awareness through persuasive communication. The purpose of this research is to analyze the persuasive communication of Peony Ecohouse in increasing environmental awareness through the Goals-Plans-Action Theory approach. This research uses the Goals-Plans-Action message production theory which was proposed by James Prince Dilliard with qualitative description research methods and collects data by in-depth interviews, observations, and documentation studies. The data was then analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. Then the data is validated through triangulation of sources. The results of this research show that the Peony Ecohouse has generated a message to raise environmental awareness. The steps taken are through goal setting, planning, and action. Peony Ecohouse has gone through this step well, but there are still things that need to be addressed as suggestions to further increase environmental awareness.